2023
DOI: 10.3389/fpls.2023.1136455
|View full text |Cite
|
Sign up to set email alerts
|

Capturing agro-morphological variability for tolerance to terminal heat and combined heat–drought stress in landraces and elite cultivar collection of wheat

Abstract: Climate change has resulted in extreme temperature and drought around the globe, which poses serious threat to food security. Both heat and drought stress affects the production and productivity of wheat crop. The present study was undertaken to evaluate 34 landraces and elite cultivars of Triticum spp. for phenological and yield-related traits under optimum, heat, and combined heat–drought stress environments during 2020–2021 and 2021–2022. The pooled analysis of variance showed significant genotype × environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…When stress occurs during grain filling, it leads to diminished starch and protein accumulation ( Bhullar and Jenner, 1985 ; Zahedi et al., 2003 ), hastened plant development, premature leaf senescence, and reduced photosynthetic rate and capacity ( Stone and Nicolas, 1995 ; Tewolde et al., 2006 ). Ultimately, these effects culminate in smaller grain size ( Wardlaw and Wrigley, 1994 ; Stone and Nicolas, 1995 ; Sharma et al., 2008 ; Talukder et al., 2014 ) and lower grain yield ( Tewolde et al., 2006 ; Talukder et al., 2014 ; Kumar et al., 2021 ; Kumar et al., 2023a ). Plants employ various major adaptive mechanisms to develop thermotolerance.…”
Section: Introductionmentioning
confidence: 99%
“…When stress occurs during grain filling, it leads to diminished starch and protein accumulation ( Bhullar and Jenner, 1985 ; Zahedi et al., 2003 ), hastened plant development, premature leaf senescence, and reduced photosynthetic rate and capacity ( Stone and Nicolas, 1995 ; Tewolde et al., 2006 ). Ultimately, these effects culminate in smaller grain size ( Wardlaw and Wrigley, 1994 ; Stone and Nicolas, 1995 ; Sharma et al., 2008 ; Talukder et al., 2014 ) and lower grain yield ( Tewolde et al., 2006 ; Talukder et al., 2014 ; Kumar et al., 2021 ; Kumar et al., 2023a ). Plants employ various major adaptive mechanisms to develop thermotolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Low TOL as well as grain yield should be taken in consideration for selection of high yielding genotypes. Dorostkar et al 35 and Kumar et al 2 revealed similar results in wheat genotypes under both conditions. According to Erdemci 36 and Shabani et al 37 STI is a more appropriate parameter to screen tolerant genotypes of chickpeas.…”
Section: Discussionmentioning
confidence: 61%
“…The selections based on MP typically boost the average performance of genotypes in both stress and non-stress conditions and fail to make a distinction between stress-tolerant and high-yielding genotypes. MP favours higher yield potential and lower stress tolerance 2 . In our studies based on HM, MRP, GMP and STI genotypes HD 2967 had the highest values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations